(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The article is aimed at shedding light on the issue of the formation of the ethnic composition of southern Uzbekistan based on the anthropological approach of L.V. Oshanin. L.V. Oshanin shows with scientific evidence that local ethnoses such as the ancient Khorezmians, Sogdians, Bactrians and Sak-Massages played an important role in the ethnogenesis of the Uzbek people. The article analyzes Oshanin’s observations on the anthropological stratification of the Uzbeks and his conclusions about the role of Arabs and Jews in the ethnic history of southern Uzbekistan. The results of the study reveal the genetic affinity and cultural ties in the historical development of the Uzbek and Tajik peoples.